Emerging roles of miRNAs in neuropathic pain: From new findings to novel mechanisms - Zhao, Yu-Ying; Wu, Zi-Jun; Zhu, Li-Juan; Niu, Tong-Xiang; Liu, Bin; Li, Jing (Frontiers in Molecular Neuroscience, 2023)
Neuropathic pain, which results from damage to the somatosensory nervous system, is a global clinical condition that affects many people. Neuropathic pain imposes significant economic and public health burdens and is often difficult to manage because the underlying mechanisms remain unclear. However, mounting evidence indicates a role for neurogenic inflammation and neuroinflammation in pain pattern development. There is increasing evidence that the activation of neurogenic inflammation and neuroinflammation in the nervous system contribute to neuropathic pain. Altered miRNA expression profiles might be involved in the pathogenesis of both inflammatory and neuropathic pain by regulating neuroinflammation, nerve regeneration, and abnormal ion channel expression. However, the lack of knowledge about miRNA target genes prevents a full understanding of the biological functions of miRNAs. At the same time, an extensive study on exosomal miRNA, a newly discovered role, has advanced our understanding of the pathophysiology of neuropathic pain in recent years. This section provides a comprehensive overview of the current understanding of miRNA research and discusses the potential mechanisms of miRNAs in neuropathic pain.